The letter to the Hebrews - O'Brien, Peter Thomas (Grand Rapids, Mich. : William B. Eerdmans Pub. Co. ; Nottingham, England : Apollos, 2010)
In this carefully crafted commentary Peter O'Brien distinctively harvests the results of recent scholarship on the letter to the Hebrews, especially in relation to the genre of the document and the flow of its discourse. --from publisher description
Authorship and canonicity -- The situation of the recipients -- Destination -- Date -- Genre -- Structure -- Exposition, exhortation, and purpose -- Hebrews in its first-century world -- Christian origins -- Introduction : God's final word to us in his Son, 1:1-4 -- The position of the Son in relation to that of angels, 1:5-2:18 -- Fix your attention on Jesus--a warning against unbelief--a promise of entering God's rest, 3:1-4:13 -- Since we have a great high priest, let us hold fast and draw near, 4:14-16 -- The Son's appointment as unique high priest, 5:1-7:28 -- The superior offering of the appointed high priest, 8:1-10:18 -- Since we have access to God through Christ's sacrifice, let us draw near and hold fast, 10:19-25 -- A call to perseverance and faith, 10:26-12:29 -- Concluding exhortations, final prayers, and greetings, 13:1-25.
Includes bibliographical references (p. xviii-xxxiii) and indexes.
Keywords: Bible. -- Commentaries